2015
DOI: 10.1021/np500897y
|View full text |Cite
|
Sign up to set email alerts
|

α-Glucosidase Inhibitors from a Xylaria feejeensis Associated with Hintonia latiflora

Abstract: Two new compounds, pestalotin 4'-O-methyl-β-mannopyranoside (1) and 3S,4R-(+)-4-hydroxymellein (2), were isolated from an organic extract of a Xylaria feejeensis, which was isolated as an endophytic fungus from Hintonia latiflora. In addition, the known compounds 3S,4S-(+)-4-hydroxymellein (3), 3S-(+)-8-methoxymellein (4), and the quinone derivatives 2-hydroxy-5-methoxy-3-methylcyclohexa-2,5-diene-1,4-dione (5), 4S,5S,6S-4-hydroxy-3-methoxy-5-methyl-5,6-epoxycyclohex-2-en-1-one (6), and 4R,5R-dihydroxy-3-metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 24 publications
0
40
0
Order By: Relevance
“…Antimicrobial metabolites like colletotric acid (Zou et al 2000), griseofulvin (Park et al 2005) and glucosidase inhibitor 3S, 4R-(? )-4-hydroxymellein (Rivera-Chavez et al 2015) were reported from endophytic fungi. Endophytic fungi are ubiquitous as well as extremely diverse in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial metabolites like colletotric acid (Zou et al 2000), griseofulvin (Park et al 2005) and glucosidase inhibitor 3S, 4R-(? )-4-hydroxymellein (Rivera-Chavez et al 2015) were reported from endophytic fungi. Endophytic fungi are ubiquitous as well as extremely diverse in plants.…”
Section: Introductionmentioning
confidence: 99%
“…During our investigations, we isolated two new compounds, pestalotin 4′-O-methyl-β-mannopyranoside (13) and 3S,4R-(+)-4-hydroxymellein (14), from an organic extract of a solid medium culture (rice). In addition, the known compounds 3S,4S-(+)-4-hydroxymellein (15), 3S-(+)-8-methoxymellein (16), coriloxine (17), and the quinone derivatives 18 and 19 were obtained [22] (▶ Fig. 3).…”
Section: Fungal Endophytes From Hintonia Latifloramentioning
confidence: 97%
“…The TD-SCF with the default solvent model was used to perform the ECD calculations of the major conformers in MeOH solution at the B3LYP/6-31G* (d) level of theory. The calculated excitation energy (nm) and rotatory strength (R) in dipole velocity (R vel ) form were simulated into an ECD curve using the Harada-Nakanishi equation (Equation (1)) as implemented in the SpecDis software [63][64][65]. All calculations were performed on the HP Cluster Platform 3000SL "Miztli.…”
Section: Computational Detailsmentioning
confidence: 99%